2022
DOI: 10.3389/fsufs.2022.720757
|View full text |Cite
|
Sign up to set email alerts
|

Traditional ecological knowledge to traditional foods: The path to maintaining food sovereignty in Hutsulshchyna

Abstract: The various ecosystems of the Carpathian Mountains spanning Europe, are a rich refuge for culturally important, endemic plant species as well as large carnivores. These biologically diverse landscapes are a principal source of subsistence to 16 million people, including various ethnographic groups. This paper focuses on a case study involving Hutsul communities, an ethnographic group of traditional pastoral highlanders, in the Southeastern Carpathian Mountains of Ukraine. Given ecosystem, climatic, and cultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
0
0
Order By: Relevance
“…The data confirm for Romania similarities with situations in other Eastern European countries. For example, a study on consumer behavior in Poland highlights statistically significant values for the "curiosity" criterion in food consumption as being very closely related to the tendency to consume these products, and the "recommend to a friend" criterion [55,[65][66][67][68]. In another study on the attitudes of young adult consumers (18-30 years) from seven European countries (Greece, Bulgaria, Romania, Slovenia, Croatia, Denmark the marquis of France) [69][70][71][72][73][74], it is reported that young people and adults from eastern European countries are more easily influenced by their friends and close relatives compared to those from western countries [31,56,[75][76][77][78][79][80].…”
Section: Results On Consumer Surveymentioning
confidence: 99%
“…The data confirm for Romania similarities with situations in other Eastern European countries. For example, a study on consumer behavior in Poland highlights statistically significant values for the "curiosity" criterion in food consumption as being very closely related to the tendency to consume these products, and the "recommend to a friend" criterion [55,[65][66][67][68]. In another study on the attitudes of young adult consumers (18-30 years) from seven European countries (Greece, Bulgaria, Romania, Slovenia, Croatia, Denmark the marquis of France) [69][70][71][72][73][74], it is reported that young people and adults from eastern European countries are more easily influenced by their friends and close relatives compared to those from western countries [31,56,[75][76][77][78][79][80].…”
Section: Results On Consumer Surveymentioning
confidence: 99%